PENGEMBANGAN MEDIA QR CODE MONOPOLY PADA MATERI NORMA, HAK DAN KEWAJIBAN UNTUK SISWA KELAS VI SD NEGERI 193 PEKANBARU - Damayanti Feronika Sihombing; Zaka Hadikusuma Ramadan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to develop a QR Code Monopoly learning media on the topic of notms, rights, and obligations for sixth-grade elementary school students and to determine the validity and responses to the developed media. Thes study employed the Research and Development (R&D) method using the ADDIE model, which was limited to the Analysis, Design, and Development stages. Data were collected through validation sheets completed by media, material, and language experts, as well as response questionnaires administered to teachers and students. The results indicated tha the QR Code Monopoly media was valid and feasible for use, as evidenced by the validation scores from media experts (96.43%), material experts (86.11%), and language experts (96.67%), as well as teacher responses (92.22%) and student responses (97.60%). Therefore, the QR Code Monopoly media is considered suitable for use as a learning medium to enhance students engagement in learning about nomrs, rights, and obligations.